Evaluation of RFID Tags to Permanently Mark Trees in Natural Populations - Marczewski, Tobias; Ma, Yongpeng; Sun, Weibang (Frontiers in Plant Science, 2016)
Long-term ecological and genetic studies in natural populations of tree species require marking techniques so that individuals can be re-visited over time, even in difficult terrain. Both GPS coordinates and physical labels have disadvantages that can make re-finding trees difficult. We tested passive and semi-active radio frequency identification (RFID) tags and readers as a means to relocate individual trees. Passive RFID tags do not provide a good solution because of low transmission power of hand-held readers and strong directionality. Semi-active RFID tags provide detection over longer distances, but also suffer from strong directionality. Active RFID tags promise an improvement over semi-passive tags, and could be evaluated in a future study. We conclude that RFID technology has the potential to improve the ability of researchers to locate individual trees repeatedly under natural conditions, and can be used in conjunction with other marking techniques such as physical tags and GPS coordinates.